The design, construction and testing of a wooden silo for grain storage (1996)
A hexagonal, double-walled, wooden silo of sides 1.2m, height 1.8m and of 7m3 capacity was designed. The walls and floor were taken as stressed skin panels. These were fabricated using Mansonia altissima for the ribs, while exterior grade structural plywood was used as sheathing. The silo was subjected to nondestructive testing in accordance with the British Standard Code of Practice CP: 112 and joints separation, consolidation movement of the foundation and floor deflection were periodically measured over a period of two weeks during which the structure was under load. At the end of the test period there was no measurable consolidation movement and the joints remained intact while the floor deflection was within permissible limit of ∆ ≤ L/180. Further testing and evaluation including subjecting the silo to loading for longer duration and taking measurements of stresses induced on the silo components are to be undertaken.